Shaping Market Perceptions: An Investigation into Macedonian Bank Stock Prices and their Drivers - Bojan Malchev; Zorica Bozhinovska-Lazarevska (Economy, Business and Development: An International Journal (EB&D), 2023)
This research paper examines the effects of return on assets (ROA), earnings per share (EPS), and audit opinion as a control variable, on the stock prices of banks in North Macedonia. The main objective of this study is to investigate the impact of these financial indicators on the stock prices of banks in North Macedonia and to what degree. To analyze this relationship, a linear multiple regression model is employed. Data were collected from the financial statements and annual reports of all 12 banks in North Macedonia over a ten-year period from 2012 to 2021. The results of the study demonstrate that audit opinion and EPS have a statistically significant impact on the stock prices of banks in North Macedonia. Specifically, the positive coefficient of the audit opinion variable indicates that audit opinion influences stock prices. Similarly, the positive coefficient of the EPS variable indicates that higher EPS leads to an increase in stock prices. However, it is important to note that when audit opinion is excluded from the model, the results change, and ROA shows a statistically significant impact on stock prices. This suggests that the inclusion of audit opinion as a control variable affects the relationship between ROA and stock prices. These findings imply that investors in the banking sector in North Macedonia consider audit opinion and EPS as crucial indicators of a bank's financial health, influencing their investment decisions. Maintaining a positive audit opinion and increasing EPS are important factors for boosting stock prices, which is valuable information for bank managers and investors. The recent changes in the format of the audit report, including the reporting of Key Audit Matters (KAM), have not yet been implemented in the domestic audit practice. As a result, auditors do not report on KAM, which may have influenced the research results in a different way. Also the small sample size can be persived as an limitation of the research. With only 12 banks in the Macedonian banking sector, the generalizability of the findings may be restricted. Future research could consider expanding the sample to enhance the representativeness of the study.
Keywords: G1; M42; 330; Banks; Stock price; Audit opinion; ROA; EPS